KIDS PRENEUR (KP), SOLUSI PENDIDIKAN KARAKTER UNTUK ANAK JALANAN KAMPUNG DAYAK, PURWOKERTO SELATAN - Purnomo, Arifin Budi; Astuti, Yuli; Amiyah, Fitriyatun; Siddiq, Muhammad Imadudin; Charis, Abdul; Nurchasanah, Siti (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2014)
Kampung Sri Rahayu (Dayak village) is a marginalized village in the town of Purwokerto with majority of the society bearing the social problems, such as prostitutes, transvestites, unemployed, beggars and street children. There are at least 200 street children in this village, and only 20 percent are able to receive education until graduated elementary school. The main factors causing educational process blocked in this village is the lack of parental support and absence of local government programs. This condition makes mental street children in Dayak village materialistic, self-sufficient and not depend on others. Therefore we need Kids Preneur (KP) as an alternative education so that street children in Dayak village still has a chance to grow up, standalone, creative based on religious character. The objectives of this program are: 1) Increase the knowledge, skills street children ofÂ Dayak village; 2) Increase environmental awareness and creative street children of Dayak village; 3) Grow the spirit of standalone and religious life street children of Dayak village. Method of implementation this program include: 1) Kids Prenuer Leadership that aims inculcate spirit of leadership and standalone on street children; 2) Kids Preneur Educative that aim to give education such as hardskill to street children; 3) Kids Preneur Innovative that aims to give softskill training, creative attitude to environmental conditions; 4) Kids Preneur Community, is a forum for the street children of Dayak village to learn the knowledge and entrepreneurship. The results and conclusions of the implementation of Kids Preneurâs programs are to improve the knowledge, skills, spirit care for environment, creative, standalone, religious and entrepreneurial character to street children of Dayak village, South Purwokerto. So that the education of the marginalized society gradually be resolved.Keywords: Education, Kids Preneur, Street ChildrenÂ